2014
DOI: 10.7717/peerj.461
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of the interaction of neuropilin-1 with heparin and a heparan sulfate mimetic library of heparin-derived sugars

Abstract: Background. Neuropilin-1 (NRP-1) is a multidomain membrane protein with soluble isoforms interacting with a complex network of other membrane receptors, their respective ligands and heparan sulfate (HS). It is involved in the development of vasculature, neural patterning, immunological responses and pathological angiogenesis.Methods. We have characterised the binding of a Fc fusion of rat NRP-1 (Fc rNRP-1) and of a soluble isoform, corresponding to the first four extracellular domains of human NRP-1, shNRP-1, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 54 publications
1
13
0
Order By: Relevance
“…Three lysines of the peptide ' 131 YLAMNKKGKLY 141 ' (Lys-125, Lys-126 and Lys-128) of FGF10 were found to be both acetylated and biotinylated (figure 9). This has been observed previously in other proteins [34,44], and is considered to be due to the local dissociation of a lysine side chain from its interaction with the polysaccharide. In the presence of the NHSacetate used in the protection step, the transiently dissociated lysine side chain becomes acetylated, and this would likely preclude its re-binding to the polysaccharide.…”
Section: Fgf7 Subfamily (Fgf3/fgf10)supporting
confidence: 70%
“…Three lysines of the peptide ' 131 YLAMNKKGKLY 141 ' (Lys-125, Lys-126 and Lys-128) of FGF10 were found to be both acetylated and biotinylated (figure 9). This has been observed previously in other proteins [34,44], and is considered to be due to the local dissociation of a lysine side chain from its interaction with the polysaccharide. In the presence of the NHSacetate used in the protection step, the transiently dissociated lysine side chain becomes acetylated, and this would likely preclude its re-binding to the polysaccharide.…”
Section: Fgf7 Subfamily (Fgf3/fgf10)supporting
confidence: 70%
“…NPR-1 can be shed as a short form composed of its extracellular domain. Both membrane-associated and free forms of NRP-1 bind heparin, with possible, still unexplored, biological consequences [ 129 ]. Robo binds heparin with low affinity (Kd equal to 650 nM) [ 86 ], the consequences of such interaction have been already described above for its ligand Slit.…”
Section: Molecular Bases and Biological Sequences Of The Interactimentioning
confidence: 99%
“…The molecular basis for these numerous interactions is not well understood, but crystal structure studies and other investigations have identified the binding sites of VEGF. Importantly, it binds negatively charged heparin [ 15 , 16 ], which raised the possibility that it might also bind nucleic acids. Here, we report that NRP1 binds miRNAs with high affinity and promotes their entry into the cell.…”
Section: Introductionmentioning
confidence: 99%